Comparative analysis of diosgenin in Dioscorea species and related medicinal plants by UPLC-DAD-MS - Yi, Tao (BioMed Central, 2014)
BACKGROUND: Dioscorea is a genus of flowering plants, and some Dioscorea species are known and used as a source for the steroidal sapogenin diosgenin. To screen potential resource from Dioscorea species and related medicinal plants for diosgenin extraction, a rapid method to compare the contents of diosgenin in various plants is crucial. RESULTS: An ultra-performance liquid chromatography (UPLC) coupled with diode array detection (DAD) and electrospray ionization mass spectrometry (ESI-MS) method was developed for identification and determination of diosgenin in various plants. A comprehensive validation of the developed method was conducted. Twenty-four batches of plant samples from four Dioscorea species, one Smilax species and two Heterosmilax species were analyzed by using the developed method. The present method presented good sensitivity, precision and accuracy. Diosgenin was found in three Dioscorea species and one Heterosmilax species, namely D. zingiberensis, D. septemloba, D. collettii and H. yunnanensis. CONCLUSION: The method is suitable for the screening of diosgenin resources from plants. D. zingiberensis is an important resource for diosgenin harvesting.